Simplify the following:
-(-5 (-2)+3 (-2-4))-3 (-2-3+6)
Group the negative terms in -2-4 together and factor out the minus sign.
-2-4 = -(2+4):
-3 (-2-3+6)-(-5 (-2)+3×-(2+4))
Evaluate 2+4.
2+4 = 6:
-(-5 (-2)+3 (-6))-3 (-2-3+6)
Multiply -5 and -2 together.
-5 (-2) = 10:
-(10-6×3)-3 (-2-3+6)
Multiply 3 and -6 together.
3 (-6) = -18:
-3 (-2-3+6)-(10+-18)
Group the negative terms in -2-3+6 together and factor out the minus sign.
-2-3+6 = 6-(2+3):
-(10-18)-36-(2+3)
Evaluate 2+3.
2+3 = 5:
-(10-18)-3 (6-5)
Subtract 5 from 6.
6-5 = 1:
-(10-18)-31
Factor out a negative sign in 10-18 in order to subtract.
10-18 = -(18-10):
-3×1--(18-10)
Subtract 10 from 18.
| 1 | 8
- | 1 | 0
| 0 | 8:
-(-8)-3×1
Multiply all instances of -1 in -(-8).
(-1)^2 = 1:
8-3×1
Multiply -3 and 1 together.
-3×1 = -3:
-3+8
Subtract 3 from 8.
8-3 = 5:
Answer: |
| 5